2022
DOI: 10.1101/2022.03.08.483326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activation of the cGAS-STING innate immune response in cells with deficient mitochondrial topoisomerase TOP1MT

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune condition where the underlying dysfunction is often unknown. Here, we identify a novel link between the mitochondrial topoisomerase TOP1MT and SLE, as a novel variant predicted to affect TOP1MT function, P193L, was identified in a family with SLE and other autoimmune diseases. Although there was no previous genetic association between TOP1MT and SLE, the role of TOP1MT as a regulator of mtDNA led us to investigate whether TOP1MT could mediate the release of m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…The TFAM paradigm suggested that other forms of mtDNA stress might also lead to mtDNA-release-mediated cGAS-STING signaling, which has turned out to be the case. Cells either lacking TOP1MT (EC 5.6.2.1) or expressing a pathogenic variant associated with lupus exhibit mtDNA release and activation of the cGAS-STING pathway (73). TOP1MT knockout cells have reduced mtDNA copy number and mitochondrial transcripts, defects in nucleoid organization, elongated mitochondria, and lower OXPHOS.…”
Section: Cgas-sting Signalingmentioning
confidence: 99%
“…The TFAM paradigm suggested that other forms of mtDNA stress might also lead to mtDNA-release-mediated cGAS-STING signaling, which has turned out to be the case. Cells either lacking TOP1MT (EC 5.6.2.1) or expressing a pathogenic variant associated with lupus exhibit mtDNA release and activation of the cGAS-STING pathway (73). TOP1MT knockout cells have reduced mtDNA copy number and mitochondrial transcripts, defects in nucleoid organization, elongated mitochondria, and lower OXPHOS.…”
Section: Cgas-sting Signalingmentioning
confidence: 99%
“…This, in turn, activates the cGAS-STING innate immune signaling pathway, which is known to be active in SLE and other autoimmune diseases. [49,60]…”
Section: Resultsmentioning
confidence: 99%
“…This, in turn, activates the cGAS-STING innate immune signaling pathway, which is known to be active in SLE and other autoimmune diseases. [49,60] SLE-associated dysregulated pathways have been linked to circadian abnormalities. Patients with SLE or those at risk of developing it often experience sleep disruptions, which significantly impact their quality of life.…”
Section: The Effects Of Sleep Deprivation On the Progression Of Autoi...mentioning
confidence: 99%
“…All imaging was performed as previously described (21). The Olympus Spinning Disk Confocal System (Olympus SD OSR) was used with the UAPON 100XOTIRF/1.49 oil objective lens.…”
Section: Imaging and Analysesmentioning
confidence: 99%
“…Beyond its role of encoding OXPHOS proteins, mtDNA is now also recognized to play an important role as an inflammatory signalling molecule when released from mitochondria. Examples of inflammatory signalling pathways that detect mtDNA-mediated include TLR9 (4,18), cGAS-STING (21,22) and the inflammasome (23,24). Notably, a recent study showed that inducible muscle-specific loss of MFN1 causes mtDNA release via early endosomes, leading to activation of TLR9/NF-kB inflammation and myopathy (4).…”
Section: Introductionmentioning
confidence: 99%